"Too much, too soon?" Early professional match exposure and career sustainability: a 10-year multileague cohort of professional female soccer players - Ebeid, I. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Debate persists about whether early professional competition compromises long-term career sustainability in youth athletes; evidence in women`s professional soccer is limited.